2011
DOI: 10.5539/ijbm.v6n9p190
|View full text |Cite
|
Sign up to set email alerts
|

Tax Evasion as a Crime: A Survey of Perception in Yemen

Abstract: This paper explores the perception of Yemeni citizens of the severity of tax evasion relative to other crimes and violations. Perception of tax evasion may somewhat explain the degree of non-compliance with the tax laws. Using data from a self-administered survey and a personnel structured interview, the results of mean and comparative analysis show that tax evasion items were ranked as the three least crimes of 30 listed crimes. Further, Tax evasion is categorized the least serious category out of six categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Thus, our findings align with the literature for the narrower case of bribery tolerance and they further expand their predictive validity by covering a much larger spectrum of 105 worldwide countries. The fact that these practices are positioned in some countries, in terms of people's perception, at the lower and middle spectrum of crimes [41][42][43], but they pave the way for the serious case of corruption, makes them even more relevant in terms of government priorities on changing public views on critical topics. The third factor related to interpersonal violence was not previously examined in association with corruption, thus further research is needed to unveil the psychological mechanisms supporting this link.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our findings align with the literature for the narrower case of bribery tolerance and they further expand their predictive validity by covering a much larger spectrum of 105 worldwide countries. The fact that these practices are positioned in some countries, in terms of people's perception, at the lower and middle spectrum of crimes [41][42][43], but they pave the way for the serious case of corruption, makes them even more relevant in terms of government priorities on changing public views on critical topics. The third factor related to interpersonal violence was not previously examined in association with corruption, thus further research is needed to unveil the psychological mechanisms supporting this link.…”
Section: Discussionmentioning
confidence: 99%
“…According to them, in many instances, underreported taxes involve low income earners. Similarly, Nor Ghani et al (2012); Malkawi and Haloush (2008); Devos (2006); and Nor Aziah et al (2011), found that taxpayers' income category has a positive association with tax noncompliance. They concluded that high income earned through misconduct and fraudulent sources encourage underreporting and increase noncompliance behaviour.…”
Section: Income Levelmentioning
confidence: 92%
“…The result of this research also indicates contrary finding for Hypothesis 5, as the taxpayers' education level shows a negative link with tax noncompliance. Many studies have indicated that adequate knowledge of tax laws, assessment, and reporting process, could lead to greater awareness of tax policies, and hence, enhance tax compliance among taxpayers (Purwanto & Indrawan, 2020;Devos, 2006;Aziah et al, 2011). This has been attributed to the fact that normally, the education level of individuals can positively influence the attitude and behaviour of a person in most circumstances.…”
Section: H5mentioning
confidence: 99%
“…Middle Eastern countries are mostly classified as developing countries and have recorded high level of tax non-compliance (Yemen Times, 2005). Nevertheless, it is evident that there is a lack of tax compliance studies in this region (Aljaaidi, Manaf, & Karlinsky, 2011;Helhel & Ahmed, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, the literature has shown that there a lack of studies on tax compliance and non-compliance. During the period from 2000 to 2010, Yemen regulated new tax laws and reforms in order to overcome the weaknesses in the tax system, but the volume of tax non-compliance is still questionable (Aljaaidi, Manaf, & Karlinsky, 2011;Al-Ttaffi, Manaf, Aljaidi, & McGee, 2011;Helhel & Ahmed, 2014).…”
Section: Introductionmentioning
confidence: 99%